DETERMINE THE TARGET TO INCREASE PRIMARY HEALTHCARE UTILIZATION IN INDONESIA'S DISADVANTAGED AREAS - Ratna Dwi Wulandari; Agung Dwi Laksono; Nikmatur Rohmah; Leny Latifah; Hadi Ashar (Universitas Airlangga, 2023)
Background: Primary health care (PHC) is the closest institution known to people in disadvantaged areas. Aims: The study determines the policy target based on the demographic characteristics to increase PHC utilization in a disadvantaged area. Methods: The cross-sectional research explored 42,644 respondents. In addition to PHC utilization, the study examined eight independent variables: residence, gender, marital, age, wealth, insurance, education, and travel time. We employed a binary logistic regression in the last stage. Results: Live in urban areas had 1.967 more likely to utilize the PHC (95%CI 1.942-1.992). Males could be 1.412 higher than females (95%CI 1.402-1.421). All marital types had more chances than never married. All education was more likely than no education. The employed had 0.972 less likely than the unemployed (95%CI 0.965-0.980). All wealth groups had less possibility than the poorest. Those with government-run insurance were likelier than other types. The â‰¤10 minutes travel time was more likely than the >10 minutes. Conclusion: There were seven policy target characteristics to increase PHC use in disadvantaged areas in Indonesia: live in a rural area, female, never married, have no education, employed, not the poorest, don't have government-run insurance, and have a travel time of more than ten minutes. Keywords: disadvantaged area, healthcare evaluation, primary health care, public health